ENSURING THE RIGHTS OF PERSONS WITH DISABILITIES IN THE MIDDLE XX CENTURY - Malyuha L.YU., Matselyukh I.A. (Taras Shevchenko National University of Kyiv, 2024)
The article examines the historical and legal experience of the establishment and implementation of the rights of persons with disabilities in Ukraine. The study analyzes the situation of disabled war veterans in the post-war period, based on archival documents and historical evidence. The research reveals the deplorable living conditions of disabled veterans, which included meager pensions, inaccessibility of rehabilitation means, housing and fuel supply problems. Particular attention is paid to the repressive policy of the Soviet authorities towards disabled war veterans, which manifested in forced relocation to prison-type special residential institutions and systematic deprivation of disability status through manipulations with medical commissions. The article highlights the contrast between official propaganda and the actual situation of persons with disabilities during the Soviet period, revealing the existence of parallel systems of institutions for the disabled - demonstrative and restricted facilities. The study emphasizes the magnitude of the problem by presenting statistical data on the number of disabled war veterans and describing systematic violations of their rights. The research underscores the importance of studying historical experience in the context of contemporary challenges associated with Russian aggression. The necessity of reforming state policy regarding persons with disabilities through the implementation of modern European approaches to protecting their rights is emphasized. Special attention is devoted to the necessity of developing military medical rehabilitation and corresponding infrastructure under ongoing conflict conditions. The study establishes the need to prioritize a social approach over a medical one in state policy regarding persons with disabilities. The importance of full integration of this category of individuals into society and ensuring all civil rights is substantiated.

У статті досліджується історико-правовий досвід становлення та реалізації прав осіб з інвалідністю в Україні. Аналізується становище інвалідів війни у післявоєнний період, спираючись на архівні документи та історичні свідчення. Дослідження розкриває жахливі умови життя ветеранів з інвалідністю, які включали мізерні пенсії, недоступність засобів реабілітації, проблеми з житлом та паливом. Особлива увага приділяється репресивній політиці радянської влади щодо інвалідів війни, яка проявлялася у примусовому переселенні до спецінтернатів тюремного типу та систематичному позбавленні статусу інваліда через маніпуляції з медичними комісіями. У статті висвітлюється контраст між офіційною пропагандою та реальним становищем осіб з інвалідністю в радянський період, розкривається існування паралельних систем закладів для інвалідів - показових та режимних. Констатовано на масштабах проблеми, наводячи статистичні дані про кількість інвалідів війни та описуючи систематичне порушення їхніх прав. Дослідження підкреслює важливість вивчення історичного досвіду в контексті сучасних викликів, пов'язаних із російською агресією. Наголошено на необхідності реформування державної політики щодо осіб з інвалідністю, впроваджуючи сучасні європейські підходи до захисту їхніх прав. Особлива увага приділяється необхідності розвитку військово-медичної реабілітації та відповідної інфраструктури в умовах триваючого конфлікту. Констатовано на необхідності пріоритезації соціального підходу над медичним у державній політиці щодо осіб з інвалідністю. Аргументовано важливість повноцінної інтеграції такої категорії осіб в суспільство та забезпечення всіх громадянських прав.
ЗАБЕЗПЕЧЕННЯ ПРАВ ОСІБ З ІНВАЛІДНІСТЮ У СЕРЕДИНІ ХХ СТОЛІТТЯ
Keywords: persons with disabilities; disabled war veterans; human rights; Soviet period; social protection; state policy; repressions; institutions; rehabilitation.; особи з інвалідністю; інваліди війни; права людини; радянський період; соціальний захист; державна політика; репресії; реабілітація.